Insect Vectors and Plant Pathogens - Butter, Nachhattar Singh; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
The history of pathogens and vectors, unique symptoms of diseases and economic importance of important viral diseases have been dealt with in the introductory chapter of this book. While highlighting the role of arthropods, nematodes, and fungi; other agents of the spread of plant pathogens have also been included. Important aspects of insect vectors with direct bearing on transmission, i.e. vector identification, biology, feeding apparatus, and mechanism of spread including control of pathogens through vectors are covered comprehensively. As aphids and other hemipterous insects are major insect vectors, the book stresses on this order. There is a focus on the transmission of determinants under different categories of the transmission mechanism. The transmission determinant paradigm comprising coat protein and helper component has been expounded with recent cases. A brief description of new diseases at least one from each genus of plant viruses has been included in this compendium to elucidate the interaction of vector and virus. Phytoplasmal etiology of pathogens has been detailed separately on account of their importance. The transmission of plant viruses through insects with biting and chewing type of mouth parts has been discussed in detail as separate chapter. The latest research in the field of mites, nematodes, and fungi as vectors of plant viruses has been included. How the phytotoxemia is different from other crop disorders, has been critically explained with support from suitable and common examples of crop disorders. The book also highlights the effects of plant viruses on their vectors. An account of classification of plant viruses has also been given for better understanding of subject matter. Likewise, the information on the electron microscope along with its use has been included so as to define the procedure of examining sub-microscopic entities. The latest developments in the management of plant pathogens through vector management have been discussed with special reference to the use of biotechnology, crop protection, and plant resistance. The book will be of value to the teachers and to researchers. It will also be useful for extension workers in managing crop disorders. Students and researchers of entomology, plant pathology, plant protection and virology disciplines will obtain the latest in the field, through this book.
Introduction: Historical Background, Symptoms, Pathogens and Economic Importance -- Historical Background -- Symptoms -- Pathogens -- Economic Importance -- Modes of Spread of Plant Pathogens -- Vertical Transmission -- Horizontal Transmission -- --Feeding Mechanism of Vectors and Plant Pathogens -- --Familiarization with Insect Vectors -- Identification and Biology -- Thysaoptera -- Diptera -- Coleoptera -- Hymenoptera -- Orthoptera -- Lepidoptera -- Dermaptera -- Dictyoptera -- Feeding Mechanism of Hemipterans -- Feeding Mechanism of Chewing Insects -- Mechanism of Transmission of Plant Pathogens -- Mites -- Nematodes -- Fungi/Plasmodiophorids Protozoa -- Mechanism of Spread of Fungi/ Bacteria/ Phytoplasma/ Rickettsia/ Nematodes/ Protozoa -- Aphids -- Identification -- Life Cycle of Aphids -- Virus Transmission Cycle -- Feeding Mechanism -- Virus Transmission -- Helper Component/Coat Protein -- Non-persistent Stylet-borne Viruses -- Non-persistent Foregut-borne Plant Viruses -- Persistent Circulative Viruses -- Circulative propagative Viruses -- Diseases caused by aphid-borne genera of plant viruses -- Aphids and Fungi -- Aphids and Bacteria -- Leaf Hoppers/Plant Hoppers/Tree Hoppers/Frog Hoppers/Psylla/ Mealy Bugs/Scale Insects -- Identification and Brief Life History -- Feeding Mechanism of Homopterans -- Transmission Determinants -- Phenomenon of Cross Protection -- Virus vector relationships -- Homopterous borne pathogens /diseases -- Mollicutes and Insect Relationships -- Mechanism of Transmission of Mollicutes -- Psyllid-borne Phytoplasma Diseases -- Rickettsia Like Organisms -- --Whiteflies -- Identification and Brief Biology -- Feeding Mechanism and Pathogen Transmission -- Virus Vector Relationship -- Begomovirus -- Crinivirus -- Role of Coat Protein in Transmission -- Diseases -- Heteropterous Bugs and Thrips -- Heteropterous bugs (True bugs) -- Thrips Identification and Brief Biology -- Thrips and Bacterial Pathogens -- Thrips and Fungal Pathogens -- Insect Vectors with Chewing Mouthparts -- Beetles -- Grasshoppers -- Bees, Wasps, and Ants -- Diptera as Vector -- Moths/Butterflies and Fungi -- Earwigs -- Cockroaches -- Mites -- Identification and Brief Biology -- Feeding Mechanism -- Pathogen Transmission -- Specificity in Transmission -- Spread of Viruses -- Diseases -- Fungal Pathogens -- Mites and Viroids -- Nematodes -- Identification and Brief Biology -- Feeding Aapparatus -- Mechanism of Pathogen Transmission -- Specificity in Transmission -- Diseases -- Nematodes and Bacteria -- Nematodes and Fungi -- --Fungi -- Introduction -- Characteristic Features of Vector Species -- Mechanism of Transmission -- Specificity -- Virus Vector Relationships -- Phytotoxemia -- Symptoms of Different Agents in Crop Plants -- Categories of Phytotoxemia -- Microorganisms and Phytotoxemia -- Distinction Between Viruses and Phytotoxemia -- Nature of Toxin -- Mechanism of Phytotoxemia -- --Plant Pathogens and Electron Microscope -- Plant Pathogens -- Electron Microscope -- Types of Electron Microscopes -- Preparation of Specimens for Examination -- Uses of Electron Microscope -- Pathogen Effects and Ecological Factors -- Pathogen Effects -- Climate /Weather Parameters and Virus-Vector-Host Interaction -- Weather Parameters and Phytoplasma -- Weather Parameters and Fungal Transmission -- Light and Bacteria -- Weather Parameters and Symptoms Expression -- Vector-Virus Management Strategies -- Vector Management Strategies -- Exclusion of Virus from Region /Country ----Use of virus free seed -- Elimination of Pathogen Through Tissue Culture/Chemicals -- Management of Vector with Chemicals----Management of vectors /invading vector population -- Cultural Measures -- Physical Control -- Alteration in Insect Vector Behavior -- Chemical Control -- Biological Control -- Integrated Pest Management -- Breaking Life Cycle of Plant Virus (New approach).
Includes bibliographical references and index.
Also available in print format.
Keywords: SCIENCE / Life Sciences / Zoology / Entomology; TECHNOLOGY & ENGINEERING / Agriculture / General; Cross protection/biotechnology for vector management; Feeding mechanism; Transmission determinants; Virus-vector interaction; Insects as carriers of plant disease; Phytopathogenic microorganisms; Electronic books